ALTERNATIVE REFRIGERANTS AND THEIR THERMOPHYSICAL PROPERTIES RESEARCH - Koichi Watanabe; Januarius V Widiatmo (Mesin, 1999)
The alternative refrigerants to be covered by the present paper include HFC (hydroï¬‚uorocarbon) refrigerants and their mixtures. Natural refrigerants such as hydrocarbons and carbon dioxide, and some new candidates such as HFEs (hydrofluoroethers), which all are non-ozone depleting substances. The authors aim to present an overview of the current state of the art with respect to several promising alternative refrigerants typically accepted in the refrigeration and air-conditioning industries in Japan. An emphasis will be given to the thermophysical properties research update that has signiï¬cantly contributed to accelerate an adoption of binary and/or ternary HFC blends in various engineering applications. An important international collaboration through the IEA-Annex 18 project will be stressed so as to explain how the thermophysicists worldwide did contribute to achieve a successful landmark on thermodynamic property modeling of HFC refrigerants and their mixtures. Some essential features of other alternatives, such as hydrocarbons, carbon dioxide, and HFEs will also be discussed based on the general technical observations.